2012
DOI: 10.3109/03630269.2012.745419
|View full text |Cite
|
Sign up to set email alerts
|

Family Planning Practices in Families with Children Affected by β-Thalassemia Major in Southern Iran

Abstract: Preventing the birth of children with β-thalassemia major (β-TM) is an important health issue. We investigated family planning practices and related factors among families with affected children. We selected a total of 569 parents from the parents of patients with β-TM who were registered at thalassemia referral clinics in southern Iran. Information was recorded regarding demographic variables, socioeconomic status and family planning practices. The correlations between family planning practice and related fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
2
4
0
1
Order By: Relevance
“…The study had explored family planning practices and related factors of couples with β-TM children. In the present study, among sexually active couples, 44.8% were currently using family planning method to prevent the birth of another child, which was quite worse compared to Haghpanah et al [11] (96.0%) and Ishaq et al [12] (65.0%) but similar to findings of Mallik et al [10] (51.8%). The difference of findings may be contributed to the consequence of community-wide education programs, as well as comprehensive screening and counseling programs operational in those counties unlike India.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The study had explored family planning practices and related factors of couples with β-TM children. In the present study, among sexually active couples, 44.8% were currently using family planning method to prevent the birth of another child, which was quite worse compared to Haghpanah et al [11] (96.0%) and Ishaq et al [12] (65.0%) but similar to findings of Mallik et al [10] (51.8%). The difference of findings may be contributed to the consequence of community-wide education programs, as well as comprehensive screening and counseling programs operational in those counties unlike India.…”
Section: Discussionsupporting
confidence: 72%
“…However, prior studies in this regard reported that despite having no desire for another child, there is high unmet need for family planning among parents of thalassemic children related to various factors such as education, religion, and economic status. [1112]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the number of newborns with beta-thalassemia has decreased, and the heavy financial burden of the disease has been mitigated by the relatively low-cost measures of premarital screening and genetic counseling [ 5 ]. However, some barriers, such as cultural factors, have hindered the implementation of a well-organized prenatal diagnostic system [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The contraceptives method would prevent pregnancy, and it is also useful for parents who did not know about an abortion program for the fetus less than 6 weeks who has been diagnosed with thalassemia. Haghpanah et al's (2013) stated that family planning and the usage of contraceptive is an effective program to prevent the birth of children with thalassemia. Wiradyana (2013) stated that determining gestational age less than 6 weeks for an abortion is quite difficult, because the prenatal diagnosis of thalassemia would be performed after 10 weeks' of gestation.…”
Section: Discussionmentioning
confidence: 99%